The Use of Jigsaw Technique to Improve Students' Reading Comprehension of Narrative Texts Via Wattpad Applcation - Uzlifatul Imamah; Ainu Zunrudiana; Uzlifatul Imamah; Ainu Zunrudiana (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2024)
Reading comprehension is one of the most important skills for reading texts. This study aims to determine the increase in students' reading comprehension when learning narrative texts used jigsaw learning techniques and Wattpad learning media. This study used pre-experimental research. The population of this study were eighth grade students at MTs Al Falah Gajah, and this study used purposive sampling, that is, the sample was taken from 30 students. The researcher gave the students a pre-test and a post-test, which were used to measure and evaluate the results of the pre-test and post-test. Learning Data collected includes as many as 60 items, including pre-test and post-test multiple-choice questions related to narrative texts. Pre-test and post-test data were tabulated and analyzed by percentage. The data were analyzed used SPSS 26. Based on the results of the analysis, scores in the pre-test were lower than the mean scores in the post-test (33.8000<67.4667). The study concluded that the use of the jigsaw technique and the Wattpad application were effective in improving students’ reading comprehension of narrative texts.